UPAYA MENINGKATKAN KINERJA PEGAWAI MELALUIHIGH PERFORMANCE WORK PRACTICES DENGANWORK ENGAGEMENT SEBAGAI VARIABEL MEDIASI (Studi Pada Pegawai Bank Jateng Cabang Temanggung) - Dewi Rachmawati; Taofik Hidajat (Magister Manajemen STIE Bank BPD Jateng, 2022)
This study aims to determine the effect of HPWP on work engagement and employee performance at Bank Jateng Temanggung Branch. The hypothesis proposed is that there is a positive relationship between HPWP and work engagement and employee performance, and the role of work engagement as a mediation between HPWP and employee performance at Bank Jateng Temanggung Branch. The subjects in this study amounted to 140 employees with data collection tools using questionnaires distributed through WA numbers. Data processing using SPSS 25.0 software for windows and obtained positive and significant results between HPWP on work engagement and employee performance. For path analysis, the value of the direct influence of HPWP on employee performance is 0.431 and the value of the indirect influence of HPWP on employee performance through work engagement is 0.360 with a total value of 0.791. To test the strength of the indirect influence of HPWP on employee performance through work engagement, it is calculated using the Sobel test and the t value obtained is 4.40705588 > 1.98 so that work engagement is able to prove its role as mediation.